Nephroprotective effects of substances of medicine food homology and traditional Chinese medicine phytochemicals against acute kidney injury - Chen, Ling; Deng, Yanyan; Hu, Jing; Gong, Xuezhong (Frontiers in Pharmacology, 2025)
Acute kidney injury (AKI) represents significant medical challenges due to its elevated rates of morbidity and mortality, with limited therapeutic options currently available. Hence, the exploration of novel medicinal treatments for AKI management remains vital. Substances of medicine food homology (SMFH), referring to substances having characteristics of both food and medicine, have been applied in China for thousands years.They could be used for daily diets and body conditioning. Traditional Chinese medicine (TCM), with its naturally derived components and demonstrated effectiveness, presents distinctive benefits in AKI treatment. Numerous studies have shown that SMFH and TCM phytochemicals could function satisfactorily with nephroprotective effects and have a significant effect on alleviating AKI as well as its complications. In this review, the pathogenesis of AKI was illustrated. We concentrated on SMFH and TCM phytochemicals against AKI and tried to summarize the underlying mechanisms in various kinds of AKI, highlighting the crucial phytochemical components in AKI prevention and therapy. Besides, strategies for SMFH and TCM phytochemicals globalization are analysed. This review comprehensively reveals that SMFH and TCM phytochemicals exhibit promising potential for AKI intervention by targeting various signal pathways and targets, which would contribute to AKI’s cognition, preventive treatments, as well as global promotion.